How useful is the golden triangle law in economics? - Škare, Marinko (Technological and Economic Development of Economy, 2014)
We explore the long term relationship between unemployment, inflation and output in the United Kingdom during 1851–2011 in search for a possible “golden triangle” connecting “natural” unemployment, price stability and strong (fast) rates of output growth. Exploring the possibility of existence of such internal macroeconomic equilibrium is important in setting and attaining these most acclaimed macroeconomic objectives. Not only could the results be applied in setting policy objectives but also unveil if low unemployment, stable prices and fast growth are supportive objectives. Preliminary results are encouraging and open the path for further research on the subject. Not a single economic policy designed on just a vague notion on the relationship between inflation, unemployment and output should be used since it will bring disaster to the economy.